2016
DOI: 10.1074/jbc.m116.718932
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Mitogen-activated Protein Kinase Kinase Kinase Kinase 4 (MAP4K4) Promotes Obesity-induced Hyperinsulinemia

Abstract: Previous studies revealed a paradox whereby mitogen-activated protein kinase kinase kinase kinase 4 (Map4k4) acted as a negative regulator of insulin sensitivity in chronically obese mice, yet systemic deletion of Map4k4 did not improve glucose tolerance. Here, we report markedly reduced glucose-responsive plasma insulin and C-peptide levels in whole body Map4k4-depleted mice (M4K4 iKO) as well as an impaired first phase of insulin secretion from islets derived from M4K4 iKO mice ex vivo. After long-term high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Moreover, attenuation of the hyperinsulinemia in genetically obese mice by treatment with streptozotocin or diazoxide reduces adipose tissue inflammation and increases insulin responsiveness 54 . Similar improvement in glucose tolerance is seen by reducing hyperinsulinemia in a mouse knockout model that impairs beta cell insulin secretion 55 .…”
Section: Hyperinsulinemia and Insulin Resistancementioning
confidence: 78%
“…Moreover, attenuation of the hyperinsulinemia in genetically obese mice by treatment with streptozotocin or diazoxide reduces adipose tissue inflammation and increases insulin responsiveness 54 . Similar improvement in glucose tolerance is seen by reducing hyperinsulinemia in a mouse knockout model that impairs beta cell insulin secretion 55 .…”
Section: Hyperinsulinemia and Insulin Resistancementioning
confidence: 78%
“…Wong et al had shown that fatty acid β‐oxidation was higher in LECs than in arterial, venous, and microvascular BECs, whereas glycolytic flux was lower, suggesting the important role of mitochondrial oxidation in LEC metabolism. Studies have also shown that Map4k4 impairs energy metabolism in ECs and promotes insulin resistance during high‐fat diet‐induced obesity and its systemic loss improves insulin sensitivity . Primary ECs that were a mixture of lymphatic and blood ECs showed enhanced glycolytic and mitochondrial respiration in the absence of MAP4K4.…”
Section: Discussionmentioning
confidence: 99%
“…[101]. The role of protein kinase Map4k4 has been further discussed in obesity-induced hyperinsulinemia and insulin resistance by promoting insulin secretion from β cells [103]. Involvement of the MAPK signaling pathways has been recently reported in mediating the beneficial effects of tartary buckwheat flavonoids on redox balance and insulin resistance in insulin-resistant HepG2 cells [104].…”
Section: Mitogen Activated Protein Kinase (Mapk) and Insulin Signalingmentioning
confidence: 99%